Soil pH and the Home Landscape or Garden - Amy L. Shober; Geoffrey C. Denny (EDIS)
SL-256, 3-page illustrated fact sheet by Amy L. Shober and Geoffrey C. Denny, explains soil pH for a homeowner audience and provides strategies to make the most of the pH in home landscapes and gardens. Published by the UF Soil and Water Sciences Department, January 2008.